GE_GERICHTE P/9685/2002 vom 13. Dezember 2006 - GE Cour de justice (2006)
FAUX INTELLECTUEL DANS LES TITRES ; INTENTION ; MÉDICAMENT ; PRÉSOMPTION D'INNOCENCE | CPP.245; LStup.20.1.3; CPP.5; LGS.11f; LStup.20.1.4; CP.20; CP.251.1; CP.146; CP.25; CP.22